EFEKTIVITAS PERMAINAN PUZZLE TERHADAP UPAYA PENINGKATAN KOGNITIF PADA LANSIA: Puzzle game effectiveness on cognitive enhancement efforts in the elderly - Asrina Pitayanti; Faqih Nafiul Umam (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Cognitive therapy needs to be given to the elderly whose function is to increase brain power, improve memory, prevent the risk of Alzheimer's disease, and decrease memory processes in the elderly. The research aims to analyze the effectiveness of puzzle games on the cognitive improvement of the elderly. Pre-experimental research design with a pretest-posttest approach. The target population is the elderly who are in the Karangwerda association with a total of 25 elderly people. The researcher chose a total sampling technique with inclusion criteria, namely elderly people aged 60 years and over, have a good visual function or wear glasses, have a full level of awareness or composition, and are willing to be respondents. The instrument used was the Mini-Mental State Examination (MMSE) questionnaire. Analysis of the results of the study using the Wilcoxon test found that there was an average difference in cognitive function before and after being given puzzle-playing therapy, namely an increase of 1.19 points. The parametric test obtained a p-value of 0.000 (p ≤ 0.05) meaning that puzzle games are effective in improving cognitive function in the elderly. It can be concluded that puzzle games are effectively used in improving the cognitive abilities of the elderly. So that they can be used as an alternative therapy that supports that all the elderly have a good cognitive function and can ultimately maintain the mental health of the elderly.